Confiance, langage, résistance - Hubert Vincent (Recherches en Éducation)
The purpose of the text is to analyze and present the notion of « passibility » specific to Jean-Francois Lyotard, who appoints and tries to identify an experience of reception.The text first shows how this notion makes sense from the diagnosis that Jean-François Lyotard regularly made of our time and its most problematic trends.He then shows how this experience of reception can be understood according to its link to a certain inventiveness of language, and its link with a critical rejection of the search for origin.Deeply dependent on Freud and on the model of the analytical cure, this analysis allows us to grasp the most important sources of confidence both in ourselves and in the world. As can be seen, the legacy of Jean-François Lyotard is not only concerned with the thesis of the end of the « great stories ».